A realist evaluation of community champion and participatory action approaches during the COVID-19 pandemic - Howlett, Neil; Fakoya, Olujoke; Bontoft, Charis; Simmons, Isobel; Miners, Lisa; Wagner, Adam P.; Brown, Katherine (Frontiers in Public Health, 2024)
Background During the COVID-19 pandemic, public health teams tried several approaches to circulate accurate health information and engage with community members to understand what they need from public health services. Two such approaches were community champions and community participatory action research (CPAR). This study evaluates two champion programmes and a CPAR programme in terms of what worked, for whom, and in what contexts, including the funding and resourcing associated with implementation. Methods Between June 2022 and June 2023, a realist evaluation of three distinct case studies (COVID-19 champions, Vaccine Champions, and CPAR programmes) in the city of Southampton in England was conducted in three stages: development of initial programme theories and collection of additional contextual information, including funding and resources associated with delivering each programme; initial programme theory testing; synthesis of final programme theories. Data was collected primarily through semi-structured interviews (n = 29) across programme and training leads, voluntary services, community organisations, volunteers, and local community members, and one focus group with local community members (n = 8). Results The City Council used £642 k from two funding awards to deliver the programmes: COVID-19 Champions £41 k; Vaccine Champions £485 k; and CPAR programmes £115 k. Twenty-eight initial programme theories were generated, which were “tested” to support, refine, or refute context-mechanism-outcome relationships, resulting finally in a set of 22 programme theories across the three programmes. Six demi-regularities were generated, each featuring in multiple programme theories, and providing data on how and why these programmes can work, and in which contexts: (1) building trust through community connections; (2) fostering relationships and collaboration; (3) provision of training and resources; (4) local community knowledge and expertise; (5) community representation and leadership; (6) appropriate communication and information sharing. Conclusion This study provides new knowledge and understanding of the factors affecting the implementation of community champion and CPAR approaches during public health emergencies. These findings suggest that representation and involvement of community members, establishing and building on trust, adequate training and resources, and clear communication from trusted community members and organisations are catalysts for meaningful engagement with communities. Evaluation registration: Research Registry identifier: researchregistry8094.